The transcription factor FOXO4 is down-regulated and inhibits tumor proliferation and metastasis in gastric cancer - Su, Linna; Liu, Xiangqiang; Chai, Na; Lv, Lifen; Wang, Rui; Li, Xiaosa; Nie, Yongzhan; Shi, Yongquan; Fan, Daiming (BMC cancer, 2014)
Background FOXO4, a member of the FOXO family of transcription factors, is currently the focus of intense study. Its role and function in gastric cancer have not been fully elucidated. The present study was aimed to investigate the expression profile of FOXO4 in gastric cancer and the effect of FOXO4 on cancer cell growth and metastasis. Methods Immunohistochemistry, Western blotting and qRT-PCR were performed to detect the FOXO4 expression in gastric cancer cells and tissues. Cell biological assays, subcutaneous tumorigenicity and tail vein metastatic assay in combination with lentivirus construction were performed to detect the impact of FOXO4 to gastric cancer in proliferation and metastasis in vitro and in vivo. Confocal and qRT-PCR were performed to explore the mechanisms. Results We found that the expression of FOXO4 was decreased significantly in most gastric cancer tissues and in various human gastric cancer cell lines. Up-regulating FOXO4 inhibited the growth and metastasis of gastric cancer cell lines in vitro and led to dramatic attenuation of tumor growth, and liver and lung metastasis in vivo, whereas down-regulating FOXO4 with specific siRNAs promoted the growth and metastasis of gastric cancer cell lines. Furthermore, we found that up-regulating FOXO4 could induce significant G1 arrest and S phase reduction and down-regulation of the expression of vimentin. Conclusion Our data suggest that loss of FOXO4 expression contributes to gastric cancer growth and metastasis, and it may serve as a potential therapeutic target for gastric cancer.